Examination of technology-enhanced statistical problem-solving tasks designed by pre-service teachers - Nadide Yılmaz (LUMAT: International Journal on Math, Science and Technology Education, 2023)
In this study, technology-enhanced statistical problem-solving tasks designed by pre-service teachers (PTs) were examined. The PTs designed 28 tasks. The designed tasks were analyzed within the context of the Considerations for Design and Implementation of Statistics Tasks (C-DIST) components. It was revealed that the tasks were mostly designed within the framework of the learning goal of “statistical questions-making interpretations based on the measures that serve to represent the data and the forms of representation” and that mostly real, multivariate and large data sets were used. In addition, it was observed that the context was employed in order to complete the prepared tasks and the tasks mostly included the entire investigation cycle. It was determined that the prepared tasks were mostly at Level B, followed by the tasks at Level A and Level C. In light of the results obtained, inferences were made for preparing PTs to teach statistics.